2022
DOI: 10.1111/jcal.12758
|View full text |Cite
|
Sign up to set email alerts
|

Procedural knowledge acquisition in a second‐year nursing course. Effectiveness of a digital video‐based collaborative learning‐by‐design activity using hypervideo

Abstract: Background While the use of digital technologies in collaborative design tasks have gained acceptance amongst educational researchers and instructors, few studies have analysed the application of video‐supported collaborative learning‐by‐design (VSC‐LBD) in the authentic setting of professional education and training. Objectives This study on VSC‐LBD investigated the learning processes and outcomes of nursing students who collaboratively used a hypervideo authoring tool to learn the procedure about urinary cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The majority of participants (72.5%) reported that digital technologies advanced knowledge acquisition in online learning environments. This result similar with [40], who reported that the preferred digital tools was video presentations, audio-visuals, game-based tools, and other digital resources. Most preferred recorded presentations for their ease of conveying information and creating an interactive atmosphere.…”
Section: The Preferred Technological Methods and Students' Opinionssupporting
confidence: 87%
See 3 more Smart Citations
“…The majority of participants (72.5%) reported that digital technologies advanced knowledge acquisition in online learning environments. This result similar with [40], who reported that the preferred digital tools was video presentations, audio-visuals, game-based tools, and other digital resources. Most preferred recorded presentations for their ease of conveying information and creating an interactive atmosphere.…”
Section: The Preferred Technological Methods and Students' Opinionssupporting
confidence: 87%
“…The majority of students preferred recorded presentations, game-based learning, and Padlet and Blackboard platforms. A quasi-experimental research by [40], also found that video-supported collaborative learning by design (VSC-LBD) in professional education and training led to superior performance compared to the control group. This study provides evidence supporting learning environments and offers practical guidance for educators on effectively using interactive video resources in a collaborative manner.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Smartphones are considered to provide enormous benefits in the field of nursing education, namely the ease of accessing e-learning. The use of elearning technology makes learning more interesting and flexible so that the efficiency and effectiveness of learning are assessed (Zhampeissova et al, 2020, Franco et al, 2021. Face-to-face learning is also able to deepen their nursing skills; however, the digital era requires nursing students to master their knowledge and skills comprehensively from both sources: e-learning and face-to-face learning (O'Connor and Andrews, 2018).…”
Section: Introductionmentioning
confidence: 99%